PENGARUH 18 TAHAPAN PENGEMBANGAN DIRI TERHADAP VALUE DIRI - Ilham Prasetya Wibowo; Aliffian Safriansyah; Muhammad Faishol Akbar; Didieo valeri yulianto; Nindya Kartika Kusmayati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The preparation of this article is intended to review the survey on the decisions of each resource person based on the statements that we have compiled by providing a link to each question, between self-value and its relation to self-development, the aim is to find out that all results based on the survey influence each other and have their respective roles. This also includes how to understand the meaning of self-value itself and explain its influence on the success of individuals in developing themselves. Based on the results of further research data, we found something unique called a correlation between the two that influence and support each other, we conclude that self-value will be proportional to the magnitude of the characteristics of the individual concerned, by now showing that the more valuable a person is, the more it will become a magnetic field itself, people like this tend to have high integrity because of the large value of self that they have. They are called pioneers